Morphology of the axial skeleton of seven bat genera (Chiroptera: Phyllostomidae) - Gaudioso, Pablo Javier (2017)
Here we present detailed descriptions and comparisons of the axial skeleton of seven species of bats belonging to five subfamilies of Phyllostomidae of different trophic guilds. The material examined consisted of 34 complete skeletons of seven species. For five of the studied species, previous descriptions have not been conducted, and for the vampires only limited information is available, so that descriptions for these species are here completed. The axial skeleton has characters that allow grouping of the species phylogenetically of the same subfamily and by feeding habits. At the same time, there are characters that associate species from different subfamilies with different types of diet or ways to obtain food.